Impact of Antineoplastic Treatment on Oral Cavity and Oropharyngeal Microbiota of Head and Neck Cancer Patients: Systematic Review - Silva, Iran Alves da (2022)
Introduction: A great diversity of microorganisms are found in the oral and oropharyngeal cavities, which are normally in homeostasis with other microorganisms and the host itself. Patients with head and neck cancer undergoing cancer treatment may trigger physiological changes in their bodies and impact in the resident microbiota. Objective: Systematically review studies on the impact of antineoplastic treatment on oral and oropharyngeal microbiota in patients with head and neck cancer. Method: Systematic review carried out between April and June 2020. Articles were searched in the Virtual Health Library, Google Scholar, PubMed and ScienceDirect databases in English, utilizing the descriptors “head and neck neoplasms”, “mouth neoplasms” and “microbiota” and “neoplasias de cabeca e pescoco”, “neoplasias bucais” and “microbiota” in Portuguese. Original articles available in full, published in the last decade (2010 to 2020), in Portuguese and English were selected. Results: 8 articles were included in this review. Most of studies have shown quantitative changes in resident microorganisms or invasion of exogenous bacteria in patients in antineoplastic treatment; uncontrolled microbiota homeostasis triggered cariogenic and inflammatory processes in the mucosa. Conclusion: Changes in the microbiome of the oral cavity and oropharyngeal resulting from antineoplastic treatment may be predisposing factors for adverse effects as the development of caries and oral mucositis.